2010
DOI: 10.1111/j.1749-0774.2010.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Derivation, characterization and differentiation of a new human embryonic stem cell line from a Chinese hatched blastocyst assisted by a non-contact laser system

Abstract: Currently worldwide attention has focused on the derivation of human embryonic stem cells (hESCs) for future therapeutic medicine. However, the majority of existing hESCs are directly or indirectly exposed to non-human materials during their derivation and/or propagation, which greatly restrict their therapeutic potential. Besides the efforts to improve culture systems, the derivation procedure, especially blastocyst manipulation, needs to be optimized. We adopted a non-contact laser-assisted hatching system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…More has been reported regarding functions for connexins in the more recently appreciated field of cancer stem cell biology (see below). Several studies have shown changes in connexin gene expression in response to immortalization [108][109][110] but have not investigated the underlying mechanism of connexin function in this situation. A decrease in GJIC with age and with senescence has also been reported [111][112][113][114], as well as changes in connexin expression during senescence [115].…”
Section: Replicative Immortalitymentioning
confidence: 99%
“…More has been reported regarding functions for connexins in the more recently appreciated field of cancer stem cell biology (see below). Several studies have shown changes in connexin gene expression in response to immortalization [108][109][110] but have not investigated the underlying mechanism of connexin function in this situation. A decrease in GJIC with age and with senescence has also been reported [111][112][113][114], as well as changes in connexin expression during senescence [115].…”
Section: Replicative Immortalitymentioning
confidence: 99%